Rotating disk electrode to measure diffusivity of metal ions and kinetic parameters in heterogeneous electrochemical reactions - Rijal, Shital Babu (Kansas State University, 2022)
Chemical reaction rates are generally amplified by using a catalyst and lowering the reaction energy barrier, or by raising the temperature or pressure of the system to increase reactants’ thermal energy. Regarding electrochemical reactions in solutions, we hypothesize that a rapidly changing electric field will enhance the Brownian motion of reactant ions to increase their effective temperature. Hence this technique, termed stochastic heating, is an attractive alternative for reaction rate enhancement. To test this hypothesis, we need to characterize the kinetics of the chemical reaction. Here we use a rotating disk electrode to measure the kinetic parameters and diffusivity of metal ions in the following electrochemical systems. We present a self-verifiable procedure to measure the heterogeneous rate constant of ferrous/ferric ions at the platinum electrode and their diffusivity in the chloride system. We determine favorable supporting electrolytes for studying silver and indium ions and for characterizing their kinetics. The quantities thus measured are trustworthy bases for comparing with modified systems to enhance the reaction rate in the presence of stochastic noise.
Keywords: Rotating disk electrode; Kinetic parameters of electrochemical reactions; Diffusivity of metal ions; Reduction oxidation processes; Stochastic heating; Electrochemistry